Navigating citizens’ involvement and participation in the pathways to public service and value co-production process - Alinsunurin, Jason P. (Animo Repository, 2023)
The active and direct involvement and participation of citizens are among the most indispensable elements in the co-production of public services. As one of the most fashionable and most promising themes relating to public service delivery across economies, co-production research is slowly yet accomplishing conceptual unpacking, coalescence and clarity; as a collaborative arrangement between various types of actors and the government, its activation, management and evaluation should attract the attention of scholars from various fields.In this chapter, we propose to revisit the literature on citizen coproduction, an umbrella concept defined as when citizens (or service users, lay-actors or service communities) actively and directly contribute their time, resources and/or knowledge in the design and delivery of public services. While coproduction has been commonly practiced in the private sector contexts (i.e. service co- creation and co-production), it has not received enough attention in the public sector until recently. Moreover, the historical persistence and inertia of public management traditions across countries also inevitably spell the extent, scope and depth at which collaborative or participatory approaches such as service coproduction can be institutionalized and dictate how public values are generated.As part of the dissertation project touching on the governance of education systems, we devote a section of the literature review on to partially introduce parental coproduction specifically in education settings. While we recognize that service construal variessignificantly across countries and levels of public management, education settings offer a particularly interesting context to investigate coproduction’s drivers and outcomes. Our review discusses that involvement and the participation of citizens are necessary pieces of the policy agenda to enhance citizens’ roles in shaping public values of civic interest.